Effect of traditional rehabilitation programme versus telerehabilitation in adolescents with idiopathic scoliosis during the COVID-19 pandemic: a cohort study - Rodrigo Mantelatto Andrade; Bruna Gomes Santana; Ariane Verttú Schmidt; Carlos Eduardo Barsotti; Marina Pegoraro Baroni; Bruno Tirotti Saragiotto; Ana Paula Ribeiro (Medical Journals Sweden, 2024)
Background: Telerehabilitation has become increasingly popular since the SARS-CoV-2 (COVID-19) outbreak. However, studies are needed to understand the effects of remote delivery of spine treatment approaches. Objectives: To verify and compare the effects of traditional rehabilitation programmes (in-person) and telerehabilitation (online) on the progression of scoliotic curvature in adolescents with idiopathic scoliosis during the COVID-19 pandemic, and to verify the acceptability, appropriateness, and feasibility among patients and physiotherapists regarding both treatments. Methods: This is a cohort study (prospective analysis of 2 intervention groups: telerehabilitation (online) and traditional rehabilitation (in-person). A total of 66 adolescents with idiopathic scoliosis were included. Recruitment was conducted through the Clinical Center in Scoliosis Care (January-December 2020). Participants were divided into 2 intervention groups: telerehabilitation (online) (n = 33) and traditional rehabilitation programme (in-person) (n = 33). Both groups also were supplied with a spinal orthopaedic brace. Scoliosis was confirmed by a spine X-ray examination (Cobb angle). Radiographic parameters measured were: Cobb angles (thoracic and lumbar). The method of Nash and Moe (thoracic and lumbar) was also evaluated based on the relationship between the vertebral pedicles and the centre of the vertebral body in the X-rays. Assessments were performed at baseline (T0) and after 6 months of the intervention protocol (T6). Patient and physiotherapist reports were evaluated on the acceptability, appropriateness, and feasibility of the interventions. Results: Adolescents with idiopathic scoliosis showed a significant decrease in the Cobb angle (main scoliotic curvature), with a 4.9° for the traditional rehabilitation programme and 2.4° for the telerehabilitation. Thoracic and lumbar Cobb angles did not show significant changes after the intervention in both groups or between groups. Thoracic and lumbar Nash and Moe scores scores also did not show significant differences after 6 months of in-person or telerehabilitation intervention, or between groups. The intervention by telerehabilitation was acceptable, appropriate, and feasible for patients and physiotherapists. Conclusion: Use of the rehabilitation programme for adolescents with idiopathic scoliosis, delivered via telerehabilitation during the COVID-19 pandemic, was encouraging for future applications due to the improved effect on reducing the Cobb angle, preventing progression of scoliosis. In addition, telerehabilitation showed good acceptability among patients and physiotherapists. Traditional rehabilitation programmes (in-person) in adolescents with idiopathic scoliosis also showed a reduction in the Cobb angle.